If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(v + 3) = -18 Reorder the terms: -2(3 + v) = -18 (3 * -2 + v * -2) = -18 (-6 + -2v) = -18 Solving -6 + -2v = -18 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2v = -18 + 6 Combine like terms: -6 + 6 = 0 0 + -2v = -18 + 6 -2v = -18 + 6 Combine like terms: -18 + 6 = -12 -2v = -12 Divide each side by '-2'. v = 6 Simplifying v = 6
| x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 | | 5(n+5)=34+8n | | f(x)=2x^3+x^2-19x+36 | | 3(x+2.5)=-7.5 | | x+6-2x-4=0 | | 9+3(2x-6)=14 | | -54=9n | | 6n-12=150 | | 3(x+2.5)=7.5 | | 4+2(a+4)=-20 | | 9x-6=2x+8 | | 4x+2(3x-6)=4 | | y=-2x-17 | | 2y+3=31 | | a+3+20=-1+3a+4 | | -10x=5x-1 | | 3=3x+3 | | 4d=-2(33+d) | | 1=3x+3 | | -1=3x+3 | | 10(-2)=-20 | | -5=3x+3 | | -2[-3x-8]=w | | m+2m-6=-12 | | x^3-6b^2+36b+72=0 | | 18=-6y+2x | | -8y-47=35 | | 0=-16t^2-50t+7 |